Proceedings of the 57th Annual Meeting of the Association for Computational Linguistics 2019
DOI: 10.18653/v1/p19-1270
|View full text |Cite
|
Sign up to set email alerts
|

Joint Effects of Context and User History for Predicting Online Conversation Re-entries

Abstract: As the online world continues its exponential growth, interpersonal communication has come to play an increasingly central role in opinion formation and change. In order to help users better engage with each other online, we study a challenging problem of re-entry prediction foreseeing whether a user will come back to a conversation they once participated in. We hypothesize that both the context of the ongoing conversations and the users' previous chatting history will affect their continued interests in futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 18 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…Our work is in line with conversation behavior analysis, where studies explore user interactions in ongoing conversations (Ritter et al, 2010) and how they signal the conversations' future trajectory, such as continued activity (Backstrom et al, 2013;Jiao et al, 2018;Zeng et al, 2019) and the risk of going awry . Different from these proposals which do not model personal interests, we study conversation recommendation for a specific user, where we measure how a user's preferences match a conversation's context.…”
Section: Related Workmentioning
confidence: 57%
See 3 more Smart Citations
“…Our work is in line with conversation behavior analysis, where studies explore user interactions in ongoing conversations (Ritter et al, 2010) and how they signal the conversations' future trajectory, such as continued activity (Backstrom et al, 2013;Jiao et al, 2018;Zeng et al, 2019) and the risk of going awry . Different from these proposals which do not model personal interests, we study conversation recommendation for a specific user, where we measure how a user's preferences match a conversation's context.…”
Section: Related Workmentioning
confidence: 57%
“…Data Collection and Preprocessing. In our experiments, we use datasets from two different platforms: the first one is released by Zeng et al (2018) containing Twitter conversations formed by tweets from the TREC 2011 microblog track data 2 covering a diverse set of topics; the other is from Zeng et al (2019), which is comprised of discussion threads about political issues on Reddit, a popular discussion website. The tweets in Twitter dataset were mainly posted from Jan 23 to Feb 8, 2011, and discussion threads in Reddit dataset were posted from Jan to Dec, 2008.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, recurrent neural networks, particularly LSTMs, that are natural methods to learn patterns from a sequence of a user's historical tweets (Cao et al, 2019;Zeng et al, 2019Zeng et al, , 2020, assume uniform time gaps between successive tweets. However, tweets can be posted at irregular time intervals (Lei et al, 2018), and varying time gaps can influence the assessment of a user's suicidality progression (Chen et al, 2018), as shown in Figure 1.…”
mentioning
confidence: 99%